Coupling damage and reliability modeling for creep and fatigue of solder joint. (August 2017) - Chen, Yunxia; Jin, Yi; Kang, Rui
Abstract: Solder joint often plays a crucial role in the normal operation of electronic equipment due to its unique material properties and harsh working condition, making it very important to carry out the accurate reliability analysis of solder joint. The low-cycle fatigue due to temperature cycling and the creep brought by continuous high temperature are two dominant failure modes of the solder joint. Current modeling methods for these two mechanisms mainly focus on failure process of each mechanism separately, with little consideration of the coupling relationship in the material properties. This paper introduces a coupling damage model considering both low-cycle fatigue and creep. The coupling relationship between these two failure mechanisms is investigated with the effects of creep strain rate on the ductility and the effects of damage on mechanical properties of solder joint. The analysis of the former mechanism concerns the fatigue parameter of Coffin-Manson model, while the latter one focuses on the applied stress increasing with the accumulation of damage. Further, considering that creep degradation rate would increase once the cumulative damage reaches a trigger threshold, a generalized cumulative damage model is developed. Based on this assumption, a reliability model for solder joint considering the uncertainty of model parameters is then proposed. Finally, a case study of a lead-free solder joint is given to validate this method. Highlights: The coupling relationship between low-cycle fatigue and creep is investigated with the effects of creep strain rate on the ductility and the effects of damage on mechanical properties of solder joint. And the coupling damage for creep and fatigue of lead-free solder joint is built. Considering the creep degradation rate increases due to the cumulative damage reaching a trigger threshold, a generalized cumulative damage model is developed. Based on the generalized cumulative damage model, a reliability model for solder joint considering the dispersion of model parameter is constructed.